Transthyretin amyloidosis in patients with spinal stenosis who underwent spinal surgery: a systematic review and meta-analysis - Tamasauskas, Domantas; Tamasauskiene, Laura (Frontiers in Neurology, 2024)
Background. Accumulation of transthyretin amyloids (ATTR) is detected in ligamentum flavum in about 1/3 of patients underwent surgery for spinal stenosis. However, the significance of this finding is not known. The aim of this systematic review and meta-analysis is to analyze the incidence and importance of ATTR in patients with spinal stenosis who underwent spinal surgery.Methods. The primary outcome measure was incidence of ATTR in patients with spinal stenosis.English language observational studies published within 10 years period were searched in Pubmed and Taylor and Francis databases.Results. Nine articles were included in the systematic review. The incidence of positive ATTR among patients who underwent lumbar spinal surgery was 48 % (95%CI 38-58 %). ATTR deposits were found in the lumbar region the most frequently. Seven studies showed that patients with positive ATTR were older than those with negative. Five studies investigated and found a significant relationship between the ligamentum flavum thickness and positive ATTR. Five studies investigated cardiac involvement among patients with positive ATTR.Conclusions. ATTR deposits are frequently found in older patients with spinal stenosis, especially in the lumbar region. The presence of ATTR deposits is related to ligamentum flavum thickness.